1999
DOI: 10.1046/j.1523-1755.1999.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

A new dimension to the Barker hypothesis: Low birthweight and susceptibility to renal disease

Abstract: LBW contributes to renal disease in this high-risk population. The association might be mediated through impaired nephrogenesis caused by intrauterine malnutrition. The renal disease epidemic in Aborigines may partly be the legacy of greatly improved survival of LBW babies over the last four decades. Disease rates should eventually plateau as birthweights continue to improve, if postnatal risk factors can also be contained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
246
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(264 citation statements)
references
References 38 publications
14
246
2
2
Order By: Relevance
“…These results are similar to findings in infants without CCHD 11. In infants without CCHD, SGA has been linked to the development of early systemic hypertension,27 type 2 diabetes mellitus,28 hyperlipidemia,28 and reduced renal function 29, 30. We hypothesize that this link is even more apparent in infants with CCHD.…”
Section: Discussionsupporting
confidence: 87%
“…These results are similar to findings in infants without CCHD 11. In infants without CCHD, SGA has been linked to the development of early systemic hypertension,27 type 2 diabetes mellitus,28 hyperlipidemia,28 and reduced renal function 29, 30. We hypothesize that this link is even more apparent in infants with CCHD.…”
Section: Discussionsupporting
confidence: 87%
“…Epidemiological studies have suggested that individuals with a birthweight <2.5 kg are at increased risk of developing end-stage renal disease [7,34] or albuminuria [6] compared to those with a birthweight >2.5 kg. Low birthweight, with fewer glomeruli, may provide a partial explanation for the excess end-stage renal disease in African Americans compared to Caucasians [7].…”
Section: Discussionmentioning
confidence: 99%
“…This combination of reduced glomerular number, reduced filtration surface area and hypertension is believed to result in an increased incidence and accelerated progression of non-diabetic renal diseases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hoy et al, first reported an odds ratio of 2.8 (95% CI, 1.26 -6.31) of macroalbuminuria among Aboriginal Australians who had been of LBW compared to NBW 68 . In this population, albuminuria was associated with a significant increase in cardiovascular and renal deaths, emphasising its' clinical relevance 69 .…”
Section: Renal Function Birth Weight and Nephron Massmentioning
confidence: 99%